A cheap self-powered UV-photodetector based on layer-by-layer arrangement of polyaniline and ZnO. (6th April 2022) - Nasirian, Shahruz; Hadizadeh, Farnaz
Abstract: The benefits of ultra-violet light (UV) for humans and plants are not hidden for anyone, but the harmful effects of long-term light illumination cannot be ignored for a safe life. Therefore, in the present study, we intend to evaluate and improve a cheap layer-by-layer UV-photodetector based on polyaniline/zinc oxide heterojunction under the rearrangement of the layers. The structure, morphology, and optical properties of the synthesized polyaniline (PANI) and Zinc oxide nanoneedles (ZN) were studied in detail. The semi-logarithmic I–V–T characteristics of the devices under rearrangement of the layers are shown nonlinear rectifying behavior, different reverse saturation current, various effective barrier heights in the interface, and Richardson constant close to the reported value for the Zinc oxide. I–V curves are revealed short-currents and high contrast ratios under different UV light power densities at zero bias, which imply a self-powered photoresponse feature in the devices. Repeatable significant photoresponsivity, high photocurrent, long-term stability, considerable UV on/off switching, and low rise/fall times of the devices at zero bias indicated that our hand-made devices could be used as a functional and reliable UV-photodetector. Finally, the results have shown that a device with PANI top layer has more remarkable photoresponsivity features compared to the other. Graphical abstract: Image 1 Highlights: CSA-doped PANI and ZnO nanoneedles layers synthesized, and two UVPs were created by changing the layers arrangement. I–V–T characteristics of the UVPs displayed rectification behavior, and the obtained Richardson constants are acceptable. I–V characteristics of the devices under UV illumination revealed a self-powered behavior. Long-term stability and performance accuracy offer significant reliability of our self-powered UVPs. A significant photo reponsivity properties achieved in the PZU.